Shaping a city : Ithaca, New York, a developer's perspective - Travis, Mack (Cornell University Press, 2018)
"This is the story of one Ithaca, New York, developer's involvement from first buying and renovating small houses to gradually expanding his thinking and projects to include a recognition of the interdependence of jobs, infrastructure, retail, housing, industry, taxation, banking, and city planning. It is the story of how he, along with other local developers, transformed a quiet, economically challenged upstate New York town into one that is now recognized as among the best small cities in the country"--